Bartonella spp. seroepidemiology and associations with clinicopathologic findings in dogs in the United States. (17th November 2021) - Lashnits, Erin; Thatcher, Brendon; Carruth, Ariel; Mestek, Anton; Buch, Jesse; Beall, Melissa; Neupane, Pradeep; Chandrashekar, Ramaswamy; Breitschwerdt, Edward B.
Abstract: Background: Improved understanding of Bartonella spp. serology in dogs may aid clinical decision making. Objective: Describe demographic and geographic patterns of Bartonella spp. seroreactivity in dogs, and describe hematologic and serum biochemical abnormalities in Bartonella spp. seroreactive and nonseroreactive dogs. Animals: Serum samples from 5957 dogs in the United States, previously submitted to IDEXX Reference Laboratories. Methods: Serum was tested using 3 indirect ELISAs for B. henselae, B. vinsonii subsp. berkhoffii, and B. koehlerae . Complete blood count and serum biochemistry panel results were reviewed retrospectively. Results: Overall, 6.1% of dogs were Bartonella spp. seroreactive. Toy breeds were less likely to be seroreactive (3.9%) than mixed breeds (7.5%; adjusted odds ratio [aOR], 0.48; 95% confidence interval [CI], 0.32‐0.72), and dogs <1 year old were less likely to be seroreactive (3.4%) than dogs 1 to 5.5 years of age (7.3%; aOR, 0.42; 95% CI, 0.23‐0.72). Dogs in the West South Central (9.8%) and South Atlantic (8.8%) regions were more likely than dogs elsewhere in the United States to be seroreactive (aOR, 2.22; 95% CI, 1.31‐3.87; aOR, 2.44; 95% CI, 1.38‐4.36). Conclusions and Clinical Importance: Demographic and geographic findings for Bartonella spp. exposure were broadly comparable to previously reported patterns.